A rare case of bilateral sequential spermatocytic seminoma - Xu, Ning (BioMed Central, 2013)
Spermatocytic seminoma (SS) is a rare testicular neoplasm characterized by a palpable, painless, slowly enlarging mass in the testis. Even more rare is a synchronous bilateral presentation. Only eight cases of bilateral SS have been reported in the literature, of which three cases were present with synchronous testis enlargement, and five were sequential. Here, we report an additional case of synchronous bilateral SS and present a comprehensive relevant literature review concerning clinical features, histopathology, and treatment.